Get To Know Osteoporosis: A Bone Disease That Is Often Recognized Late : Literature Review - Aceh, Hadana Khair; Nasution, Jeihan Julayka; Marniati, Marniati (Journal Hygeia Public Health, 2025)
Introduction: Osteoporosis is a systematic bone disease marked by low bone mass and deterioration of bone microarchitecture, increasing the risk of fractures. Often undetected until a fracture occurs, osteoporosis can cause significant physical, psychological, and social impacts. Objective: This literature review aims to identify risk factors, impacts, and prevention strategies for osteoporosis based on 30 scientific articles published between 2015–2025. Method: The study used a literature review method by reviewing and summarizing relevant articles and then analyzing them narratively. Results and Discussion: The results show that osteoporosis is closely related to age, estrogen decline, inactive lifestyle, low calcium and vitamin D intake, glucocorticoid usage, low body mass index, and caffeine consumption. Prevention includes proper nutrition education, healthy lifestyle, bone density screening, and osteoporosis-specific exercises, which can aid in reducing the risk of fractures. Conclusion: Osteoporosis is a significant health concern that can be effectively prevented and managed, emphasizing the importance of prevention and early detection to enable individuals to maintain a healthy and independent life.